The Optimization of Education and Training Programs to Enhance Auditor Performance Within Itwasum Polri - Yulianto, David; Syamsunasir, Syamsunasir (Dinasti Publisher, 2025)
This study explores the optimization of education and training programs to enhance auditor performance within Itwasum Polri. Auditors play a critical role in ensuring accountability and effectiveness within organizational operations. However, gaps in skills and knowledge can impede their performance. This research aims to identify the effectiveness of current education and training methods and propose strategies for improvement. Using qualitative and quantitative methods, the study evaluates training outcomes and their impact on auditor performance. The findings reveal significant improvements in auditor efficiency and accuracy following targeted training interventions. The study concludes that a tailored education and training framework can substantially elevate the performance of auditors, ensuring better organizational outcomes.